Краткий обзор и определительная таблица видов рода Micropterix (Lepidoptera, Micropterigidae) Палеарктики. I. Морфологический очерк и результаты изучения типового материала видов, описанных X. Г. Амзелем - Козлов, М.В. (Вестник зоологии, 1988)
A short reYiew of morphology, biology, distribut ion and foss il records of the genus Micropterix H b n., is given. M. aureatella shikotanica ssp. n. is descr ibed fro m Kuril islands (Sh ikotan). M. octopunctella Ams e I, M. islamella Ams e I and M. igaloensis AmseI are redescribed; M. nurhagella AmseI and M. limbarella AmseI are suggested to be nomina dubia.